La expropiación en la legislación ecuatoriana - Alomoto Guamaní, Gloria (2016)
This research work deepens the understanding of the Expropriation; the study of the Ecuadorian legislation that regulates; cases where applicable. Let you know the expropriation procedure with the mediate purpose of being useful to all those interested on this strictly legal action. The study presents several concepts of expropriation, determines its entirety. It refers to the difference with other legal forms. It deals with the regulation of Expropriation making COOTAD. The research concludes that the cases where expropriation must be exhaustively stated in the Act. The affected by this figure should receive fair compensation. It must tend to a direct arrangement between the expropriating authority and the owner of the property, not to get to trial. The process of expropriation must be agile and can not be an instrument of abuse of power. In the research process several resources, mainly the consultation of books, theses, papers, expert testimony, websites, etc. were used There was significant personal contribution.